ESTIMATION OF FLUX LINKAGE OF PERMANENT MAGNET SYNCHRONOUS MOTOR USING KALMAN FILTER (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
The real flux linkage value on the rotor side of a permanent magnet synchronous motor (PMSM) determines the field control performance of the motor. The flux linkage in the rotor side is taken into consideration as a constant parameter for half of the full order observer and stator flux estimate. However, realistically speaking, flux linkage can vary across a large range. A new set of variables is established for internal permanent magnet synchronous motors, or IPMSMs. A third order Kalman filter is developed by taking into account a set of additional variables as well as the state variables of the rotor flux linkage. By using Ld=Lq, the flux linkage of the rotor side for a surface-mounted PMSM may be shown. The model is simulated using FEM to evaluate the effectiveness of the proposed approach. The computed findings indicate the precision of the flux linkage on the rotor side.
Keywords: Permanent magnet synchronous motor (PMSM); Space vector pulse width modulation (SVPWM); Kalman filter; Flux linkage; Finite element method (FEM)